1994
DOI: 10.1152/ajpregu.1994.266.1.r151
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide synthesis suppresses sleep in rabbits

Abstract: The effects of N omega-nitro-L-arginine methyl ester (L-NAME), an inhibitor of nitric oxide synthesis, on spontaneous and interleukin-1 (IL-1)-induced sleep were examined in rabbits. Animals were injected intracerebroventricularly or intravenously during the light phase with vehicle, L-NAME, IL-1, or the combination of L-NAME and IL-1. Injection of L-NAME (5 mg icv and 100 mg/kg iv) suppressed both non-rapid eye movement sleep (NREMS) and rapid eye movement sleep (REMS) for 4-6 h. The sleep-suppressive effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 0 publications
4
47
0
Order By: Relevance
“…It is possible that ghrelin's wake-and feeding-promoting effects are mediated through MPA nitric oxide (NO). NO-producing mechanisms are implicated in the regulation of sleep (20) and feeding (33). Microinjection of a NO-donor into the MPA increased arousal (45).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that ghrelin's wake-and feeding-promoting effects are mediated through MPA nitric oxide (NO). NO-producing mechanisms are implicated in the regulation of sleep (20) and feeding (33). Microinjection of a NO-donor into the MPA increased arousal (45).…”
Section: Discussionmentioning
confidence: 99%
“…The site of sleep-suppressing action of L-NAME is not known, although various brain stem structures may possibly play a role. Evidence for the brain stem site of action of NO arose from microinjection experiments where pontine administration of NOS inhibitors decreased NREMS and REMS amounts in rats (21,25) and in cats (10), and injection of N G -nitro-L-arginine into the medial pontine reticular formation decreased REMS in cats (30). Furthermore, injection of NO donors (10,21) or the NO precursor L-arginine (21) into the pedunculopontine tegmental nucleus elicited increases in NREMS and REMS.…”
Section: Discussionmentioning
confidence: 99%
“…There has been some controversy in the literature regarding the effects of L-NAME on sleep. Although the majority of the experiments reported thus far have shown that systemic administration of NOS inhibitors such as L-NAME (24,27,35,36,40), 7-NI (7,17), or 3 bromo-7-NI (15) suppress sleep, in contrasting reports, increased NREMS and/or REMS amounts were found in response to systemic injection of the NOS inhibitors L-NAME (7) and L-NMMA (16). In the latter studies, the NOS inhibitors were administered at dark onset or during the dark period.…”
mentioning
confidence: 99%
“…The LPS-induced fever was attenuated by Dex, a potent inhibitor of the transcription of iNOS (Rees et al, 1990;Szabo et al, 1994;Wu et al, 1995) high dose (5000 gg) of L-NAME in rabbits (Kapas et al, 1994). L-NAME and L-NMMA are equally potent inhibitors of eNOS from porcine endothelial cells (Rees et al, 1990).…”
Section: Discussionmentioning
confidence: 99%